Case Report: Breast cancer in pregnancy with placental metastasis - Lin, Yongming; Xie, Xinru; Wang, Jiayi; Chen, Hongbing; Wan, Ningning; Lin, Jianqing (Frontiers in Oncology, 2025)
With the increasing incidence of breast malignant tumours in the population, some rare cases of breast cancer have been reported. We would like to share with you a case of placental metastasis of a malignant tumour of the breast: the patient was a young woman who was diagnosed with a breast cancer at 31 weeks of gestation. After regular follow-up, a healthy baby girl was delivered by caesarean section at 37 weeks of pregnancy. In a subsequent placenta specimen, the pathologist found distant metastasis of breast cancer to the placenta. This is rare in distant metastases of breast cancer. The patient is currently undergoing further anti-tumour therapy. Through reviewing the relevant literature, we have compiled and discussed the mechanisms related to the possible use of placenta in preventing cancer invasion and how breast cancer in pregnancy can be followed up. We hope that sharing this case will help further clinical and experimental research.